Characterization of the evolution of long non-coding RNAs in the developing cerebral cortex transcriptome - Morales Vicente, David Abraham (2022)
The human outstanding cognitive abilities are computed in the cerebral cortex. This mammalian-specific brain structure has been the place of massive biological innovations throughout evolution. Over the past decade, long non-coding RNAs (lncRNAs) have emerged as gene regulatory elements with greater tissue-specificity and evolutionary turnover than mRNAs. lncRNAs are highly expressed in neural tissues, making them candidates for cerebral cortex plasticity, evolution, and disease. Whether changes in the expression or the de novo expression of lncRNAs have impacted the development and evolution of the human cerebral cortex remains an open question. To characterize the evolutionary changes of lncRNAs in the developing cerebral cortex, we used system biology approaches to comprehensively annotate the repertory of lncRNAs in humans, rhesus macaques, mice, and chickens; and to identify the syntenic conservation of the cortical lncRNA repertory in the human transcriptome, classifying human lncRNAs into evolutionary groups as a function of the predicted minimal age. Those groups of lncRNAs showed differences in genomic and regulatory features and expression dynamics, indicating differences in their functionality. By combining single-cell RNA-seq and weighted gene co-expression network analysis, the cellular context of the innovation of the lncRNAs repertory was unveiled; older lncRNAs showed preferential expression in early neurodevelopmental stages and germinative zones, while newer lncRNAs showed preferential expression in synaptogenic glutamatergic neurons and Human-specific gene co-expression modules. Additionally, newer lncRNAs were dysregulated in autism spectrum disorders, a Human-specific disease. These results highlight the de novo expression of lncRNAs as genetic sources of cerebral cortex evolution, especially for the diversification and dysfunction of glutamatergic neurons.